ANALISIS YURIDIS PENERAPAN SANKSI PIDANA TERHADAP PELAKU PEMBAKARAN LAHAN DALAM BEBERAPA PUTUSAN HAKIM DIKAITKAN DENGAN ASAS KEADILAN - Maysarah Maysarah; Evi Deliana; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The act of burning land is prohibited under article 69 paragraph (1) letter h of Law No.32 of 2009 concerning Environmental Protection and Management, article 56 paragraph (1) ofLaw No. 39 of 2014 concerning Plantations, and articles 187 and 188 of the Criminal Code. Thecriminal act of burning land does not look at the area of land that has been burned, even thoughit is only a narrow size, the perpetrators can already be punished. In practice, as long as there isa fire that burns the land, it is a criminal act. And arrests were made immediately regardless ofthe area of land burned, the status of the perpetrators and the culture of the community. Thejudge decided to follow the consideration of the public prosecutor. In the case of burning, issue680/Pid.B-LH/2019/PN Rhl on behalf of Mujito, issue number 631/Pid.B-LH/2019/PN Rhl onbehalf of Muhammad Fauzi and issue number 29/Pid.B-LH/2019 /PN Rhl on behalf of Muarnialias Ujang Kulal Bin Kulal. Arson occurred in the same area, the public prosecutor was thesame and was decided by the same judge but the sentences were different.The purpose of this study is to find out how the application of criminal sanctions toperpetrators of land burning crimes. and how the laws and regulations against the perpetratorsof land burning. This research is structured using the type of normative juridical research,namely research that formulates the application of the principles or norms in positive law. Theapproach used is a normative approach, namely library law research.The judge decided to follow the consideration of the public prosecutor. In the case ofburning, issue 680/Pid.B-LH/2019/PN Rhl on behalf of Mujito, issue number 631/Pid.B-LH/2019/PN Rhl on behalf of Muhammad Fauzi and issue number 29/Pid.B-LH/2019 /PN Rhlon behalf of Muarni alias Ujang Kulal Bin Kulal. There was burning in the same area but thepunishment was different. That the imposition was based on the consideration of the publicprosecutor. And the public prosecutor determined the indictment based on the objectives of theperpetrators of the land burning and the status of land ownership. regardless of the area ofburned land, the type of burnt land, burned plants and community customs. Weaknesses in thelaws and regulations related to the criminal act of burning land are contained in the Legislationcontained in the removal of the prohibition of